Land-Use Planning and Management Strategies for a Sustainable Greater Jabotabek - Douglass, Mike (Journal of Regional and City Planning, 1996)
Land-use strategies for a sustainable Greater Jabotabek focus attention on balancing economic and social requirements with those for maintaining the integrity of the natural environment. Two levels, region—wide planning and community—level land—use planning, are included. Region-wide land—use planning seeks to guide the direction and from of urban expansion lo minimize impacts on environmentally sensitive areas, notably uplands and coastal zones, to maintain sufficient natural amenities such as open spaces, and to provide land for environmental infrastructure and services. A critical need at the community level is to provide sufficient supplies of serviced land for housing to keep pace with the rapidly growing residential population of Jabotabek. Both scales of planning can be enhanced by expanding local and regional scale capacities for planning and monitoring land development.